Glories of ancient Chang-an - Inoue, Masatsugu; Iyuki, Hajime; Noguchi, Takutaro; Tamai, Isao (The Silk Road, 1990)
Explore Xi-an, formerly Chang-an, the starting point of the Silk Road and the world's largest city when it was the capital of Tan Dynasty China in the seventh century. Presents the clay army of Emperor Qin Huang Di who united China and built the Great Wall. Buried for almost 2,000 years, the unearthing of the Clay Army was an archaeological triumph. Includes the sculptures of Emperor Gao-zong's tomb, the world's largest tomb 50 miles west of Xi-an, China's most hallowed Buddhist temple, Great Wall and the hidden underground murals of Princess Yong-tai.